The Realization of Academic Freedom as the Basis of Assurance of Higher Education Quality - Svyatov, Serik Amanzholovich; Adambekova, Ainagul Amangeldinovna; Amankeldi, Nazigul Amankeldikyzy (International Journal of Economics and Financial Issues, 2015)
The organization of management in the higher education institutions of Kazakhstan according to essential new standards, which are being dictated by the reforming of national high education, has forced are think of the problem of academic freedoms as a fundamental principle of university life. While the situation with the understanding of university autonomies and its influences on the private high education institutions continue to remain ambiguous. Problems of independence are actual not only for the state, but also for private high education institutions as well. However, there is no clear understanding of academic freedoms in these universities. This work reflects the author’s opinion concerning the prospects of the realization of the academic freedoms of teachers and students in post Soviet countries. Keywords: academic freedom, universities, autonomy, university management JEL Classifications: I23, I22, I28